Fatsia Japonica-Derived Hierarchical Porous Carbon for Supercapacitors With High Energy Density and Long Cycle Life - Li, Huiling; Cao, Lihua; Wang, Feng; Duan, Gaigai; Xu, Wenhui; Mei, Changtong; Zhang, Guoying; Liu, Kunming; Yang, Meng; Jiang, Shaohua (Frontiers in Chemistry, 2020)
Fatsia Japonica mainly composed of glucose have potential as porous carbon matrix precursor for supercapacitors to achieve high value utilization. A cost-effective hierarchical porous carbon materials (HPC) were prepared from Fatsia Japonica by annealing at high temperature. The pore size and distribution of HPC can be precisely controlled and adjusted by altering the activation temperatures. The obtained HPC at 600 oC showed favorable features for electrochemical energy storage with a surface area of 870.3 m2/g and a pore volume of 0.257 cm3/g. The HPC for supercapacitors (three electrode system) exhibited good specific capacitance of 140 F/g at current density of 1 A/g and a long cycling life stability (87.5% remained after 10000 cycles). In addition, the HPC electrode showed an excellent energy density of 23 Wh/Kg. Such hierarchical porous biomass carbon would be good electrode candidates for supercapacitor application due to the simple preparation and the fascinating electrochemical performance.